Case Report: A Novel Activating FLT3 Mutation in Acute Myeloid Leukemia - Bruno, Samantha; Bandini, Lorenza; Patuelli, Agnese; Robustelli, Valentina; Venturi, Claudia; Mancini, Manuela; Forte, Dorian; De Santis, Sara; Monaldi, Cecilia; Grassi, Alessandra; Chiurumbolo, Gabriella; Paolini, Stefania; et al. (Frontiers in Oncology, 2021)
FMS-like tyrosine kinase 3 (FLT3) is among the most common driver genes recurrently mutated in acute myeloid leukemia (AML), accounting for approximately 30% of cases. Activating mutations of the FLT3 receptor include internal tandem duplications (ITD) that map to the auto-inhibitory juxtamembrane (JM) domain or point mutations within the tyrosine kinase domain (TKD). Several FLT3 tyrosine kinase inhibitors have been developed in the last few years, but midostaurin is currently the only one approved for the treatment of newly diagnosed patients harboring FLT3 mutations. Here we describe for the first time a novel in-frame deletion in exon 14 (JM domain) of the FLT3 gene, that we identified in a young woman with CBFb-MYH11-positive AML. We demonstrated that this novel FLT3 variant is pathogenic, since it is responsible for constitutive activation of FLT3 receptor. Finally, ex-vivo studies demonstrated that this novel mutation is sensitive to midostaurin.